PERSISTENT PNEUMOTHORAX IN A PREMATURE INFANT (Zdravstveni glasnik, 2024)
Introduction: Pneumothorax is a condition in which the air is present in the pleural space with a collapse ofthe ipsilateral lung. Spontaneous pneumothorax is divided into primary and secondary. Primarypneumothorax makes 80% of all pneumothoraxes and there are no pathological changes present in the lungs.Secondary pneumothorax is a condition in which there is a lung disease in the background. A rare cause ofsecondary pneumothorax in premature infants is a bronchopleural fistula, which is a pathologicalcommunication between the bronchi and the pleural space.Objective: Indicate the need for early diagnosis and evaluation of secondary pneumothorax in order to carryout the early optimal treatment of the patient.Case report: Male premature infant, born from a high-risk pregnancy, gestational age of 31+6/7 weeks, lowbirth weight, presented with respiratory failure due to the respiratory distress syndrome, and persistentpneumothorax with the accompanying ventilation difficulties. Given the relapsing nature of the disease andlimited compensatory mechanisms in premature neonates, a thoracotomy was indicated and abronchopleural fistula of the upper section of the right lung was verified. The congenital pathologicalcommunication between the bronchi and pleural space was corrected by surgical procedure. The procedurewent well same as the postoperative recovery on the department.Conclusion: Congenital bronchopleural fistulas are rare and big issue in premature neonates. Clinical sign,suggesting a bronchopleural fistula, is a persistent and relapsing pneumothorax, which - if left untreated -would lead to the obstructive shock and heart failure due to the collapse of the compensatory mechanisms.Rapid diagnostic and therapeutic approach is important for having a good outcome for our patients.